Calculating the appropriate prophylactic dose of cefazolin in women undergoing cesarean delivery. (3rd July 2022) - Fouks, Yuval; Ashwal, Eran; Yogev, Yariv; Amit, Sharon; Ben Mayor Bashi, Tali; Sinai, Noa; Firsow, Anastasia; Hasson, Eyal; Gamzu, Ronni; Many, Ariel
Abstract: Background and Objectives: Surgical site infection and other postoperative complications are relatively common in obstetrical procedures, and they are associated with morbidity, prolonged hospital stay, and readmissions. Appropriate levels of antimicrobial agents given directly before skin incision can prevent the establishment of surgical-related infection caused by endogenous microorganisms present on the woman's skin. We aimed to determine serum concentrations of cefazolin given to pregnant women prior to scheduled cesarean delivery and to compare their drug concentrations and pharmacokinetics in 2 weight groups. Study Design: We conducted a prospective cohort analysis of the pharmacokinetics of cefazolin in women undergoing cesarean delivery (August 2017 to September 2018). One or two grams of intravenous cefazolin was administered within 30 min prior to skin incision to women weighing <80 kg and ≥80 kg, respectively. Maternal serum samples were obtained at skin incision and 30 min later. The serum concentration of cefazolin was measured by high-pressure liquid chromatography. Antimicrobial coverage was defined as being appropriate when the cefazolin levels were above the minimal inhibitory concentration. Pharmacokinetic parameters were estimated using a one-compartment model. Results: A total of 61 women were enrolled, of whom 47 underwent cesarean delivery (study group). The mean time that had elapsed between drug administration to incision was 13 ± 6.9 min (95% confidence interval 10.6–16.2 min). The drug levels after 30 min in women who weighed >80 kg and in women who received 2 g cefazolin, after 30 min from incision differed significantly (87.0 ± 26.0 vs 55.4 ± 16.6 μg/ml, p = .0001). Conclusion: A single 1- or 2-g dose of cefazolin provides serum concentrations above minimal inhibitory concentrations for susceptible pathogens in most women undergoing scheduled cesarean delivery.